Detrital zircon evidence for the ternary sources of the Chinese Loess Plateau. (15th April 2018) - Sun, Jimin; Ding, Zhongli; Xia, Xiaoping; Sun, Min; Windley, Brian F.
Graphical abstract: Highlights: Detrital zircon ages of deserts and loess in the Chinese Loess Plateau are presented. The Tarim, Junggar and Qaidam Basins are not important sources of the Loess Plateau. There are three potential sources for the loess on the Loess Plateau. Abstract: The provenance of Chinese loess is fundamental for understanding its origin, transportation and climatic significance. In this paper, eight samples were collected for detrital zircon age analysis, five from different deserts, and three from the Jingbian Section in the northern Chinese Loess Plateau, covering an age range of 2.6–0.03 Ma. The new results, integrated with knowledge of relevant topography and wind patterns, demonstrate that the age spectra of the detrital zircons in the loess are different from those of the sands from the Tarim, Junggar and Qaidam basins, implying that these basins were not the sources of the silts of the Loess Plateau. Further analysis suggests that the three sources for the loess are: (1) clastic materials eroded from the mountains of the Central Asian Orogenic Belt (especially the Gobi Altai and Hangay), (2) clastic loess-sized materials generated by erosion of the Qilian Mountains in the NE Tibetan Plateau, and (3) minor clastic debris derived from the mountains of the North China Craton. Thus, silts of the Loess Plateau have a complex origin, although inland basins, long believed to be important sources, have only a minor role at most.